TRIM31 Deficiency Is Associated with Impaired Glucose Metabolism and Disrupted Gut Microbiota in Mice - Cheng, Jing; Xue, Fei; Zhang, Meng; Cheng, Cheng; Qiao, Lei; Ma, Jing; Sui, Wenhai; Xu, Xingli; Gao, Chengjiang; Hao, Panpan; Zhang, Meng; Zhang, Yun (Frontiers in Physiology, 2018)
Abstract: Tripartite motif-containing protein 31 (TRIM31), an E3 ubiquitin ligase of the tripartite motif family, plays an important role in the innate immune response. It can reduce the activity of the nucleotide-binding oligomerization domain-like receptor (NLR) family pyrin domain containing 3 (NLRP3) inflammasome. However, little information is about glucose metabolic health of TRIM31-deficient mice, and investigations about gut microbiota in TRIM31-deficient mice is limited. Thus, we aimed to compare glucose metabolic parameters, gut microbiota composition and inflammatory cytokine levels between TRIM31-/- and wild-type (WT) mice, and further investigate whether or not certain gut microbiota taxon correlates with specific metabolic parameters and inflammation cytokines in TRIM31-deficient mice. TRIM31-/- mice showed glucose intolerance and insulin resistance, with a significant difference in gut microbiota composition, characterized by increased abundance of Prevotellaceae and Veillonellaceae. TRIM31-/- mice with impaired glucose metabolism was accompanied by elevated serum tumor necrosis factor-α (TNF-α) and interleukin 1β (IL-1β) concentrations, as well as upregulated caecal TNF-α, IL-1β, caspase-1 and NLRP3 expressions. Furthermore, elevated p-IRS-1/IRS-1 protein expression, and decreased Akt Thr308 phosphorylation were observed in TRIM31-/- mice. Prevotellaceae abundance was positively associated with caecal IL-1β mRNA expression, and Veillonellaceae was associated with higher TNF-α mRNA expression and serum insulin concentration. In conclusion, our study is novel in showing that TRIM31 deficiency is associated with impaired glucose metabolism and disrupted gut microbiota in mice. This study contributes to the theoretical foundation on the potential relationship between TRIM31 deficiency and the development of abnormal glucose metabolism.